Targeting shikimate pathway for antimycobacterial drug discovery using traditionally used medical plants - Matotoka, Mashilo Mash (My University, 2022)
Respiratory tract infections (RTIs) are frequent ailments among humans and are a high burden to public health. One strategy for the development of new therapies against pathogenic bacteria such as Mycobacterium tuberculosis is to target essential biosynthetic pathways of its metabolism. The aim of this study was to evaluate and target the biosynthesis of aromatic amino acids (shikimate pathway) of Mycobacterial spp using medicinal plant extracts. The selection of the plants in this study was based on their ethnopharmacological use for the treatment of tuberculosis infections and related symptoms. The leaves were dried at ambient temperatures and ground to fine powder. The powdered material was extracted with hexane, dichloromethane, acetone, methanol and water. Phytochemical screening was done using standard protocols that tested for tannins, saponins, terpenoids, alkaloids, flavonoids, steroids, anthraquinones, phlobatannins, quinones, and betacynins. Phytochemical fingerprints were established using thin layer chromatography (TLC) where three mobile phases varying in polarity were used to develop the chromatograms. Total Phenolics, flavonoids, flavonols, tannins, alkaloids and proanthocyanidin contents were quantified using UV/Vis spectrometry. Spectrometric quantification of the free radical (DPPH) scavenging activity and ferric (potassium ferricyanide) reducing power were performed. The heat-dependent bovine serum albumin and egg albumin denaturation assays were used to evaluate anti-inflammatory activity. Antimycobacterial activity was screened using bioautography assay in qualitative analysis. Quantitatively, broth microdilution assay was used to determine the minimal inhibitory concentrations. The Clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 interference genetic editing technique was used to evaluate and validate the essentiality of the aromatic amino acids in Mycobacteria to further determine the vulnerability and draggability of the transketolase (tkt) and DAHPs (aroG) genes. Plasmid, PLJR962, was used for the CRISPRi/dCas9 gene knockdown experiments. The integrating CRISPRi plasmid expressed both sgRNA with the targeting region (for tkt or aroG) and the dCas9 handle which is under control of the anhydrotetracycline (ATC) inducible promoters. The spot assay and growth curves were used to for phenotypic characterisation and gene knockdown experiments. RNA microarray (qPCR) was used to evaluate the level of expression inhibition of tkt gene . Mechanism of action of plants extracts bioactive components were predicted based on synergy between gene knockdown, shikimate inhibitors and the plant extracts. To evaluate whether the shikimate intermediates may rescue gene depleted M. smegmatis hypomorphs, the cultures were grown in L-tryptophan, L-phenylalanine, L-tyrosine and shikimic acid and growth curves constructed. Cytotoxicity of the extracts was evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay on Vero cell lines and phorbol 12-myristate 13-acetate (PMA) differentiated THP-1 macrophages. Phytochemical analysis showed that the various extracts had various polar and non-polar compounds which belonged to phenolics, saponins, steroids, terpenoids, alkaloids, cardiac glycosides and resins. Numerous non-polar compounds from Gardernia volkensii, Senna petersiana, Ficus sur had antimycobacterial activity against M. smegmatis in bioautography. Remarkably, acetone extracts from S. petersiana, Acacia senegal, Carissa bispinosa, P. africanum and C. gratissimus that had moderate to low antimycobacterial activity against wild type M. smegmatis (mc2 155) demonstrated improved inhibitory activity against the tkt PAM1 M. smegmatis CRISPRi mutant. Only the acetone Clerodendrum glabrum, Croton gratissimus, Peltophorum africanum and Gardenia volkensii demonstrated activity against M. tuberculosis H37Rv. These results suggest that the employment of CRISPRi in M. tuberculosis to develop screening models may increase changes of obtaining bioactive chemical species because the tkt gene knockdown was showed to possess the ability to potentiate the antimycobacterial activity of the plant extracts. An added advantage of the plant extracts is their antioxidant and anti-inflammatory activities which may benefit the host immune system during treatment of infection by reducing free radicals and pro-inflammatory agents that perpetuate the infection. Non polar compounds were found to generally have higher anti-inflammatory activity than the polar counterpart for all the plant extracts. These results suggest that the non-polar compounds from the tested extracts may not only confer antimycobacterial effects, but also anti-inflammatory activities. A. senegal, G. volkensii, F. sur, S. petersiana and C. glabrum were found to be toxic to the Vero cell line. However, purification techniques may circumvent their toxic effects. This study demonstrated that the amino acid biosynthesis is a potential antimycobacterial drug target because it was found to be essential, vulnerable and druggable by medicinal plant extracts
Thesis (Ph.D.(Microbiology)) -- University of Limpopo, 2022
Keywords: Mycobacterium tuberculosis; biosynthetic; Phytochemical; Respiratory tract infections; Respiratory infections; Medicinal plants; Traditional medicine; Mycobacterium tuberculosis